Isolated Crohn's Colitis: Is Localization Crucial? Characteristics of Pediatric Patients From the CEDATA–GPGE Registry - Elonen, Lotta; Wölfle, Lena; de Laffolie, Jan; Posovszky, Carsten; , the CEDATA–GPGE-Study-Group; Schwerdt, Tobias; Ganschow, Rainer; Trenkel, Stefan; Rodeck, Burkhard; Wirth, Stefan; Zurek, Marlen; Heiduk, Matthias; et al. (Frontiers in Pediatrics, 2022)
Introduction: Paediatric patients with inflammatory bowel disease (IBD) are classified into Crohn's disease (CD), ulcerative colitis (UC) and unclassifiable (IBD-U). However, data provide evidence that ileal CD (L1) is distinct from colonic CD (L2). The aim of this study was to investigate the clinical features of isolated Crohn's colitis in a paediatric population. Material and Methods: Children who were prospectively included in the CEDATA-GPGE registry upon diagnosis were compared according to the diagnosis of CD with L2 versus L1 and ileocolonic (L3) involvement pattern as well as IBD-U and UC. The clinical significance of L2 was investigated with regard to extraintestinal manifestations, treatment, surgery, and disease activity. Results: Fifty-two patients CD with L2 at a median age of 13.4 years (3.8SD) were compared with 182 L1 (13.82.9SD), 782 with L3 (12.83.3SD), 653 with UC (12.73.8SD) and 111 patients with IBD-U (11.94.7SD). Bloody stools at diagnosis were more common in L2 (44%) than in L1 (19.7%) and L3 (28.8%), but not as common as in UC (66.5%) and IBD-U (61.3%). Fewer CD patients with L2 (10.2%) received exclusive enteral nutrition therapy (EEN) as induction than patients with L1 (34.3%) and L3 (33.3%). After induction therapy, 42.3% of patients with L2 received immunosuppressants and 21% biologicals during follow-up (L1 56.5%/10.5%; L3 59%/21%; CU 43.5%/11.9%; IBD-U 26.1%/12.6%). Extraintestinal manifestations were more frequent in L2 (23.1%) versus L1 (18.7%), L3 (20.2%), CU (15.8%) and IBD-U (11.7%). The number of patients requiring surgery did not differ within the CD subgroups and was significantly lower in UC and IBD-U. Perianal fistula surgery was significantly more common in L2 (44%) than in L1 (4.8%) or L3 (21.7%). In addition, the frequency of surgery for perianal abscesses was also more frequent in L2 (55.6%) than in L1 (12.7%) or L3 (38.4%). Conclusion: The consideration of paediatric Crohn's colitis as a distinct disease seems necessary as it is characterised by extraintestinal manifestations (EIM) with mainly joint involvement and perianal fistulas or abscesses requiring surgery and biologic therapy. Thus, colonic Crohn's disease may have an influence on the therapeutic stratification and should be addressed in further studies.